Hypertensive retinopathy revisited: some answers, more questions. Issue 12 (18th November 2005) - Grosso, A; Veglio, F; Porta, M; Grignolo, F M; Wong, T Y
Abstract : Hypertension is associated with cardiovascular risk and systemic target organ damage. Retinopathy is considered one of the indicators of target organ damage. This review focuses on recent studies on hypertensive retinopathy and their implications for clinical care. Early recognition of hypertensive retinopathy signs remains an important step in the risk stratification of hypertensive patients.